Low preference for Sabah Tea by domestic consumers in Kota Kinabalu, Sabah, Malaysia / Kamal Adzi and Agnes Paulus Jidwin - Adzi, Kamal; Paulus Jidwin, Agnes (2008)
Sabah Tea is one of the few products locally produced in Sabah by Desa Tea Sdn. Bhd. Prompted by the curiosity on why some domestic consumers have low preference towards Sabah Tea, a survey was conducted to find out the factors that influenced the domestic consumers' low preference towards the product. In addition, this study also looks into the strengths and weaknesses of the company; identify ways to overcome the weaknesses and exploit the strengths as well as to recommend strategies to increase Sabah Tea Company's market share. Based on the convenient sampling technique, a total of 200 local consumers around Kota Kinabalu and the surrounding areas were chosen as respondents. The team also conducted interviews with the management of the company. Results from the survey indicate that the domestic consumers' low preference towards Sabah Tea is being influenced by its quality, price, promotion and distribution. In addition, Sabah Tea is confronting threats and weaknesses that can only be dealt with by the company strengths and opportunities. In dealing with the threats and weaknesses faced by the company, Sabah Tea must take advantage of its marketing, human resource and the company's production strengths to take on the potential threats such as economic uncertainty, environmental damage, competitors' challenges and to minimize the weaknesses confronted by the company such as lack of infrastructure facilities. At the same time Sabah Tea can also use its internal strength factors to tap into the available opportunities such as involving in free trade agreement and acquiring new sophisticated tea processing machinery for long term production efficiency and effectiveness.